Micro/nano topological modification of TiO2 nanotubes activates Thy-1 signaling to control osteogenic differentiation of stem cells - Li Jinsheng; Deng Qing; Chen Junhao; Si Qiqi; Chen Jieru; Yang Liwen; Guo Zhiyun; Guo Tailin; Weng Jie (SLAS Discovery, 2024)
Micro/nano topological modification is critical for improving the in vivo behaviors of bone implants, regulating multiple cellular functions. Titania (TiO2) nanotubes show the capacity of promoting osteoblast-related cell differentiation and induce effective osseointegration, serving as a model material for studying the effects of micro/nano-topological modifications on cells. However, the intracellular signaling pathways by which TiO2 nanotubes regulate the osteogenic differentiation of stem cells are not fully defined. Thy-1 (CD90), a cell surface glycoprotein anchored by glycosylphosphatidylinositol, has been considered a key molecule in osteoblast differentiation in recent years. Nevertheless, whether the micro/nano topology of the implant surface leads to changes in Thy-1 is unknown, as well as whether these changes promote osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Here, TiO2 nanotubes of various diameters were prepared by adjusting the anodizing voltage. qPCR and immunoblot were carried out to assess the mechanism by which TiO2 nanotubes regulate Thy-1. The results revealed Ti plates harboring TiO2 nanotubes ∼100-nm diameter (TNT-100) markedly upregulated Thy-1. Subsequently, upregulated Thy-1 promoted the activation of Fyn/RhoA/MLC Ⅱ/F-actin axis, which enhanced the nuclear translocation of YAP. After Thy-1 knockdown by siRNA, the Fyn/RhoA/MLC Ⅱ/F-actin axis was significantly inhibited and TiO2 nanotubes showed decreased effects on osteogenic differentiation. Therefore, Thy-1 upregulation might be a major mechanism by which micro/nano-topological modification of TiO2 nanotubes promotes osteogenic differentiation in BMSCs. This study provides novel insights into the molecular mechanism of TiO2 nanotubes, which may help design improved bone implants for clinical application.